2013
DOI: 10.1039/c3tb20784f
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione-capped fluorescent gold nanoclusters for dual-modal fluorescence/X-ray computed tomography imaging

Abstract: The development of efficient multifunctional nanoprobes for tumour imaging has become a great challenge. Herein, we report for the first time the synthesis of folic acid (FA)-conjugated glutathione (GSH)-capped gold nanoclusters (Au NCs) for dual mode fluorescence/X-ray computed tomography imaging of gastric cancer. Water-soluble GSH-capped Au NCs were synthesized by using tetrabutylammonium borohydride (TBAB) as the reducing agent, and was characterized by transmission electron microscopy, UV-vis absorption s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 106 publications
(69 citation statements)
references
References 34 publications
2
65
1
Order By: Relevance
“…In our previous work, with the aim of finding early gastric cancer, we screen out some new biomarkers associated with early gastric cancer and develop novel ultrasensitive detection methods [8][9]. We also designed and fabricated some multifunctional nanoprobes for targeted imaging and simultaneous therapy of subcutaneous and in situ gastric cancer tissues with 5 mm in diameter [10][11][12][13][14][15][16][17][18][19][20][21][22]. Among those multifunctional nanoprobes, RGDconjugated gold nanorods could target tumor tissues and kill tumor cells via photothermal therapy [14], exhibiting potential clinical application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, with the aim of finding early gastric cancer, we screen out some new biomarkers associated with early gastric cancer and develop novel ultrasensitive detection methods [8][9]. We also designed and fabricated some multifunctional nanoprobes for targeted imaging and simultaneous therapy of subcutaneous and in situ gastric cancer tissues with 5 mm in diameter [10][11][12][13][14][15][16][17][18][19][20][21][22]. Among those multifunctional nanoprobes, RGDconjugated gold nanorods could target tumor tissues and kill tumor cells via photothermal therapy [14], exhibiting potential clinical application prospects.…”
Section: Introductionmentioning
confidence: 99%
“…[134,135] On a mice model, using GS-GNPs functionalized with FA, Zhang et al confirmed the possibility to image cells in-vitro, and to selectively image induced tumors in-vivo. [136] This system has been proven to be almost not toxic to tested cells (human gastric cancer MGC-803 and gastricepithelial GES-1) and showed good biocompatibility in-vivo as well.…”
Section: In-vitro Applicationsmentioning
confidence: 98%
“…For instance, Zhang et al reported a novel synthetic approach for synthesizing FA-conjugated GSH-AuNCs, and explored their single fluorescence imaging (FI) and X-ray computed tomography (CT) imaging capabilities. The dual-modal FI and CT imaging for cells showed that this FA conjugated GSH-AuNCs were promising fluorescent probes [138]. Furthermore, FI and magnetic resonance imaging (MRI) dual-modal imaging through coupling AuNCs with paramagnetic agents is also very popular [139].…”
Section: Biological Imagingmentioning
confidence: 99%